Cooperation in Respect to Military Security in Asia and Pacific Region - Skulski, Przemysław (Współpraca wojskowa w regionie Azji i Pacyfiku, 2010)
With the end of the Cold War, perception of security issues changed considerably. Whereas in the period of the so-called "bi-polar order", national security was associated mainly with military aspects, from the 1990s onward there has been a marked shift towards extending the security issues with others problems. Despite this trend, military aspects still play a major role in national security policies. The Asia-Pacific region still remains a "hot subject" from the standpoint of global military balance. This applies both to areas of armed conflict (Afghanistan) as well as regions of potential threats (such as the relations between India and Pakistan, China and Taiwan, and the latent conflict on the Korean Peninsula). For these reasons, nations of the Asia-Pacific region put the issue of military security cooperation very high on the list of their priorities.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 134, s. 156-166
Keywords: military security; international security organizations; bilateral cooperation